ANALISIS STILISTIKA HADIS PENDIDIKAN DALAM ASPEK KIASAN DAN KOHESI - Nasrun Salim Siregar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to analyze the stylistics of educational hadiths, focusing on the aspects of figurative language (metaphor) and cohesion. The main objective of this study is to identify and explain the use of figurative language and cohesion elements found in hadiths related to education. Hadith, as a primary source of Islamic teachings, often uses figurative language that requires deep interpretation to understand its true meaning, particularly in the context of education. Through a stylistic approach, this research seeks to unravel the beauty and rhetorical strength of hadith in conveying educational messages. This study is a library research, which involves examining secondary references, namely the hadiths of the Prophet (peace be upon him), as well as secondary references such as hadith explanations and other hadith-related books. The results of the study show that educational hadiths often use strong metaphors to describe abstract concepts such as knowledge, teachers, and students. Additionally, the cohesion elements in these hadiths play a crucial role in maintaining the unity of ideas and facilitating the understanding of the messages being conveyed. The cohesion identified includes the repetition of key terms, explicit references, and the use of parallel sentence structures. This research contributes to a deeper understanding of the structure and stylistic power of hadiths, particularly in the educational context, and emphasizes the importance of language analysis in the study of hadith.